Exercise intensity during wheelchair rugby training - Barfield, J. P.; Malone, L. A.; Arbo, C.; Jung, A. P. (Journal of Sports Sciences, 2010)
The purpose of this study was to determine the ability of individuals with a cervical spinal cord injury to achieve and sustain a cardiorespiratory training intensity during wheelchair rugby. Nine wheelchair rugby players completed a continuous peak exercise test on a SciFit Pro I arm ergometer with stage increases each minute to determine peak heart rate and power output. Approximately one week after peak exercise testing, heart rate was recorded (every 5 s) during three regularly scheduled rugby training sessions. Data were analysed to determine the number of continuous minutes that participants spent above 70% of heart rate reserve under various rugby training activities. The percent of time spent at or above 70% heart rate reserve varied across participants and conditions. Continuous pushing was the least variable training condition among participants with the sample averaging greater than 73% of time above the target heart rate. Scrimmage training was highly variable across participants with a range of 0% to 98% of time above the criterion. Results of this study indicate that wheelchair rugby training enables some participants to reach a training intensity associated with improved cardiorespiratory fitness, and that the type (or kind) of training activity dictates the extent to which individuals sustain such a threshold.